2017
DOI: 10.1002/ecy.1946
|View full text |Cite
|
Sign up to set email alerts
|

Environmental drivers of coral reef carbonate production and bioerosion: a multi‐scale analysis

Abstract: The resilience of coral reefs depends on the balance between reef growth and reef breakdown, and their responses to changing environmental conditions. Across the 2500-km Hawaiian Archipelago, we quantified rates of carbonate production, bioerosion, and net accretion at regional, island, site, and within-site spatial scales and tested how these rates respond to environmental conditions across different spatial scales. Overall, there were four major outcomes from this study: (1) bioerosion rates were generally h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 62 publications
(182 reference statements)
2
24
0
Order By: Relevance
“…Parrotfish biomass at outer sites in Maunalua, although low (parrotfish biomass= 0.2 ± 0.2 g m −2 at Black Point, 1.3 ± 0.5 g m −2 at Wailupe), is comparable to other open or unprotected sites on O'ahu (Williams et al ), and higher than the inshore sites included in this study, where no adult parrotfish were observed throughout the experiment (K. Lubarsky unpubl.). Indeed, the bioerosion rates at the outer sites are comparable to bioerosion rates found on reefs throughout the Hawaiian archipelago (Silbiger et al ).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Parrotfish biomass at outer sites in Maunalua, although low (parrotfish biomass= 0.2 ± 0.2 g m −2 at Black Point, 1.3 ± 0.5 g m −2 at Wailupe), is comparable to other open or unprotected sites on O'ahu (Williams et al ), and higher than the inshore sites included in this study, where no adult parrotfish were observed throughout the experiment (K. Lubarsky unpubl.). Indeed, the bioerosion rates at the outer sites are comparable to bioerosion rates found on reefs throughout the Hawaiian archipelago (Silbiger et al ).…”
Section: Discussionsupporting
confidence: 75%
“…This is consistent with previous studies that have noted increased bioerosion with increasing nutrients (Edinger et al ; Holmes 2000; Le Grand and Fabricius ). Studies that have assessed bioerosion rates in the Hawaiian Archipelago have found the highest bioerosion rates at Kahekili, Maui, a site with a significant influx of nutrient‐rich SGD (Prouty et al ; Silbiger et al ), indicating that the relationship between SGD and bioerosion in the current study is not a localized phenomenon.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Numerous efforts have been conducted along West Maui, Hawaii, USA, to characterize and quantify submarine groundwater discharge (SGD) and associated nutrient input (Dailer et al, 2010Glenn et al, 2013;Swarzenski et al, 2013Swarzenski et al, , 2016Silbiger et al, 2017), which may influence reef metabolism and community composition by changing coastal water quality. Building upon these studies, we present a comprehensive study to characterize the carbonate system parameters from the reefs in this area.…”
Section: Introductionmentioning
confidence: 99%